Singapore : Financial Sector Assessment Program; Technical Note-Crisis Management, Resolution, and Safety Nets. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2019)
This technical note on Crisis Management, Resolution, and Safety Nets on Singapore highlights that the resolution tools are well designed, with the exception of bail-in powers; however, steps are still needed to operationalize the resolution plans. The note reviews current practices, considering international best practice principles as outlined in the Financial Stability Board's Key Attributes for Effective Resolution of Financial Institutions and the International Association of Deposit Insurers' Core Principles Effective Deposit Insurance Systems. Monetary Authority of Singapore currently develops resolution plans for Domestic Systemically Important Bank only. The resolution plans for each institution must be reviewed for both internal consistency and cross-institutional consistency. Some extension of resolution planning should be considered. The funding arrangements for resolution aim at limiting public sector exposure to loss. Losses will be first borne by equity holders and unsecured subordinated creditors. When additional funds are required, the deposit insurance fund, built by ex-ante premiums from members, can be used to support the resolution of members on an equivalent cost basis.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet